2016
DOI: 10.4218/etrij.16.0115.0228
|View full text |Cite
|
Sign up to set email alerts
|

LTE-Based Passive Bistatic Radar System for Detection of Ground-Moving Targets

Abstract: Use of a passive bistatic radar (PBR) system in the surveillance or monitoring of an area has its advantages. For example, a PBR system is able to utilize any available signal of opportunity (for example, broadcasting, communication, or radio navigation signals) for the purposes of surveillance. With this in mind, there are potentially many research areas to be explored; in particular, the capability of signals from existing and future communication systems, such as 4G and 5G. Long‐Term Evolution (LTE) is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Multipath signals for each RRU/MS are generated randomly in cluster, mimicking reflected/scattered signals from objects. Multipaths in each cluster are generated following uniform distributions of [10,15] for the total multipath number, [0, 45] degrees for direction span, [0, 45] m for distance, and [0, 600] Hz for Doppler frequency. Across clusters there are additional offsets in direction ([−75, 75] degrees), distance ([50, 180] m) and moving speed ([−40, 40] m/s), reflecting the different locations of the transmitter to the sensing receiver.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multipath signals for each RRU/MS are generated randomly in cluster, mimicking reflected/scattered signals from objects. Multipaths in each cluster are generated following uniform distributions of [10,15] for the total multipath number, [0, 45] degrees for direction span, [0, 45] m for distance, and [0, 600] Hz for Doppler frequency. Across clusters there are additional offsets in direction ([−75, 75] degrees), distance ([50, 180] m) and moving speed ([−40, 40] m/s), reflecting the different locations of the transmitter to the sensing receiver.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The five sensing parameters in (3) can be estimated either individually or jointly by forming from 1D to 4D CS models. In this paper, we propose to use 1D compressive sensing based on the on-grid formulation in (10), as will be detailed in Section IV and V, mainly for the following three reasons:…”
Section: E Selection Of Compressive Sensing Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, Raja Syamsul et al used Long-Term Evolution (LTE) in a passive dual-base radar application. The feasibility study and experimental results of using cellular signals as source signals showed that LTE signals could be used as source signals [3]. Due to the vastly available radar frequency band, large array aperture, and fast electromagnetic wave propagation, integrated radar communication systems often use operating regimes, such as time-sharing, frequencysharing, and split-beam.…”
mentioning
confidence: 99%